Hydrostatic stress and hydrostatic stress gradients in passivated copper interconnects - Ang, Derrick (2011)
A numerical evaluation of the effects of geometrical factors on the hydrostatic stress and hydrostatic stress gradients in passivated copper interconnects was performed. These values were correlated with experimental values in the literature on the location of voids in the interconnect. Copper interconnects of aspect ratios between 0.1 and 10 were studied. Numerical work using the commercial ANSYS software and analytical work based on the Eshelby andWikstr¨om models were performed. Comparison is made between the analytical, numerical and experimental results (obtained from the literature). It was found that for an interconnect with no pre-existing voids, maximum hydrostatic stress gradients occurred at the corners of the interconnects suggesting that void growth is most probable at the corners of the interconnect. The stress gradient within the interconnect with aspect ratio of 10 is about 10 times larger than that in interconnects of aspect ratios 0.1 and 1. This suggests that the narrowest interconnects are most likely to undergo voiding. This study found that it is insufficient to look only at the hydrostatic stress at the centre of the interconnect and that stress gradient also needs to be taken into consideration to assess reliability.